Waffen im festlichen Saal, eine griechisch-italische Sitte - von Ungern-Sternberg, Jürgen (Hyperboreus, 2022)
Meeting in dining-halls for a symposium was a widespread habit in ancient Greece and Italy. Especially remarkable was their frequent decoration with real weapons, which is not only described in some literary texts, but also testified by archeological findings. Outstanding is the Tomba di Rilievi di Cerveteri which looks like an illustration of a famous poem of Alcaeus.